Immunization with Bacillus Spores Expressing Toxin A Peptide Repeats Protects against Infection with Clostridium difficile Strains Producing Toxins A and B - Permpoonpattana, Patima (American Society for Microbiology, 2011)

(untitled)
Clostridium difficile is a leading cause of nosocomial infection in the developed world. Two toxins, A and B, produced by most strains of C. difficile are implicated as virulence factors, yet only recently has the requirement of these for infection been investigated by genetic manipulation. Current vaccine strategies are focused mostly on parenteral delivery of toxoids. In this work, we have used bacterial spores (Bacillus subtilis) as a delivery vehicle to evaluate the carboxy-terminal repeat domains of toxins A and B as protective antigens. Our findings are important and show that oral immunization of the repeat domain of toxin A is sufficient to confer protection in a hamster model of infection designed to closely mimic the human course of infection. Importantly, neutralizing antibodies to the toxin A repeat domain were shown to be cross-reactive with the analogous domain of toxin B and, being of high avidity, provided protection against challenge with a C. difficile strain producing toxins A and B (A(+)B(+)). Thus, although many strains produce both toxins, antibodies to only toxin A can mediate protection. Animals vaccinated with recombinant spores were fully able to survive reinfection, a property that is particularly important for a disease with which patients are prone to relapse. We show that mucosal immunization, not parenteral delivery, is required to generate secretory IgA and that production of these neutralizing polymeric antibodies correlates with protection. This work demonstrates that an effective vaccine against C. difficile can be designed around two attributes, mucosal delivery and the repeat domain of toxin A.